2020
DOI: 10.1111/gfs.12461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen application rate on productivity, nutritive value and winter tolerance of timothy and meadow fescue cultivars

Abstract: In Finland, there seems to be a substantial amount of unutilized production capacity in grassland cultivation that can, and should, be better used in the future. Ley farming is generally based on three-year leys, harvested two or three times per year for silage. Timothy and meadow fescue are the two most common species used in forage grass production in Finland. Nitrogen (N) is the most important nutrient in yield formation of grasses. Dry matter (DM) yield responses of perennial cool-season grasses to fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…The increase in silage CP concentration from first harvest through to third harvest (118, 121 and 140 g/kg DM, respectively: p < 0.001) is comparable to the CP concentrations reported by Termonen et al. (2020), and likely reflects the increasingly vegetative stage of herbage harvested as the season progresses, as indicated by the decreasing NDF and ADF concentration of the silages. It is suggested that increasing ash concentrations with later harvests ( p < 0.001) may reflect increasing soil contamination of crops or soil contamination being less “diluted” within lighter crops later in the season.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The increase in silage CP concentration from first harvest through to third harvest (118, 121 and 140 g/kg DM, respectively: p < 0.001) is comparable to the CP concentrations reported by Termonen et al. (2020), and likely reflects the increasingly vegetative stage of herbage harvested as the season progresses, as indicated by the decreasing NDF and ADF concentration of the silages. It is suggested that increasing ash concentrations with later harvests ( p < 0.001) may reflect increasing soil contamination of crops or soil contamination being less “diluted” within lighter crops later in the season.…”
Section: Resultssupporting
confidence: 81%
“…For example, protein is an essential nutrient for livestock production, and lower protein concentrations in silages may necessitate increased concentrations of protein supplementation via concentrates. However, silage protein is readily degradable in the rumen (Termonen et al., 2020), and if the ammonia arising from its breakdown is not captured efficiently by rumen microbes, much will be excreted in manure. Thus lower protein silages may actually result in improved N use efficiency in ruminants, albeit with additional costs associated with concentrate purchases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in Nieznanice, in spite of the lowest values of most of the analysed traits, in the samples taken the crude protein content was found to be the highest. Such a relationship, indicating a high level of amino acids as protein precursors, most probably was connected with a high level of soil available nitrogen, which had been suggested by other researchers in their earlier studies on timothy (Arvidsson et al, 2013;Pomerleau-Lacasse et al, 2019;Termonen et al, 2020). Besides the AE interaction, the most important information obtained due to experiments at many locations, the AMMI biplot, also gives a chance for visualization of the accession main effect in different environments (Bocianowski et al, 2018).…”
Section: Total Accession Selection Indexmentioning
confidence: 66%
“…Nitrogen fertilization can improve forage productivity and forage crude protein (Delevatti et al., 2019; Termonen et al., 2020). However, use of N fertilizer leads to losses of NH 3 , nitrous oxide, and nitrate (Zaman, Saggar, Blennerhassett, & Singh, 2009).…”
Section: Introductionmentioning
confidence: 99%